2020
DOI: 10.3389/fphys.2020.544559
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Impairment of Postural, Physical, and Muscular Functions Following Downhill Compared to Level Walking in Older People

Abstract: Transient symptoms of muscle damage emanating from unaccustomed eccentric exercise can adversely affect muscle function and potentially increase the risk of falling for several days. Therefore, the aims of the present study were to investigate the shorterand longer-lasting temporal characteristics of muscle fatigue and damage induced by level (i.e., concentrically biased contractions) or downhill (i.e., eccentrically biased contractions) walking on postural, physical, and muscular functions in older people. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 87 publications
(119 reference statements)
2
5
0
Order By: Relevance
“…The lack of change in any balance metric may be indicative that the eccentric exercise did not induce muscle fatigue, possibly a consequence of the low metabolic demand (Hoppeler 2016 ). To the authors’ knowledge, only Hill et al ( 2020 ) have assessed the short-term effects of eccentric exercise on older adults’ postural stability, reporting that immediately after 30 min of downhill walking their postural stability was unaffected, which concurs with the findings of the present study. Conversely, Hill et al ( 2020 ) also reported that balance was impaired at 24 and 48 hr post-exercise, although these disparate findings are likely a consequence of the exercise volume and/or type of eccentric exercise as Hill et al ( 2020 ) prescribed a substantial volume to induce muscle damage (downhill walking for 30 min), unlike the present study that utilised 5 min on a recumbent stepper.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The lack of change in any balance metric may be indicative that the eccentric exercise did not induce muscle fatigue, possibly a consequence of the low metabolic demand (Hoppeler 2016 ). To the authors’ knowledge, only Hill et al ( 2020 ) have assessed the short-term effects of eccentric exercise on older adults’ postural stability, reporting that immediately after 30 min of downhill walking their postural stability was unaffected, which concurs with the findings of the present study. Conversely, Hill et al ( 2020 ) also reported that balance was impaired at 24 and 48 hr post-exercise, although these disparate findings are likely a consequence of the exercise volume and/or type of eccentric exercise as Hill et al ( 2020 ) prescribed a substantial volume to induce muscle damage (downhill walking for 30 min), unlike the present study that utilised 5 min on a recumbent stepper.…”
Section: Discussionsupporting
confidence: 90%
“…To the authors’ knowledge, only Hill et al ( 2020 ) have assessed the short-term effects of eccentric exercise on older adults’ postural stability, reporting that immediately after 30 min of downhill walking their postural stability was unaffected, which concurs with the findings of the present study. Conversely, Hill et al ( 2020 ) also reported that balance was impaired at 24 and 48 hr post-exercise, although these disparate findings are likely a consequence of the exercise volume and/or type of eccentric exercise as Hill et al ( 2020 ) prescribed a substantial volume to induce muscle damage (downhill walking for 30 min), unlike the present study that utilised 5 min on a recumbent stepper. Collectively, these data indicate that the volume of exercise may be an important variable to control when prescribing specific eccentric exercise modes for older adults and that multi-joint low-volume and submaximal eccentric exercise can be performed by older adults without short-term reductions in static balance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A trial by Hill et al fits the pre-determined eligibility criteria [ 21 ]. The findings of the paper suggested that eccentric interventions increase the risk of falls and degrade functional performance in older adults.…”
Section: Aims and Objectivesmentioning
confidence: 99%
“…First, given the high muscle forces that can be achieved during the eccentric phase, this exercise may cause temporary muscle damage. Muscle damage resulting from eccentric exercise can lead to muscle weakness, postural instability, and impaired physical function which can persist for several days, endangering older adult's safety during daily activities and potentially increase the risk of falls (13). Second, although coordination and technical demand of flywheel exercise may increase the risk of injury, the use of a harness and holding onto a secure structure for balance, as used in this study, likely reduces the technical skills necessary for proper movement execution.…”
Section: Practical Applicationsmentioning
confidence: 99%